Prevalence of Endocrinopathies in Beta Thalassemia Major Patients attending Al-Faihaa Specialized Endocrine Center at Al-Basra City - Al - Hamdi, Ghasaq K.I.; Issa, Sajjad S. Issa; Mansur, Abbas A. (Indonesian Journal on Health Science and Medicine, 2025)
Background: Endocrine disorders in patients with thalassemia are one of the most common complications, and the burden of excessive iron overload and suboptimal chelation therapy mainly causes them. The prevalence is very high; however, determining it is almost impossible due to the wide range of heterogeneity among people and the varying times of exposure to chelation agents. Aim: To find out the prevalence of endocrinopathies and their types among patients with Beta-thalassemia major. Patients and Method: A retrospective descriptive cross-sectional study, in which the data of 172 thalassemia major patients who consulted the AL-Faihaa Specialized Endocrine, Metabolism and Diabetes Center (FSEMD) during the period from the first of September 2008 to the first of July 2017, were analyzed, and the results were obtained. Results: The study showed that out of 172 patients with Beta-thalassemia major, endocrinopathies were reported in 165 (95.9%) of them. Growth hormone (GH) deficiency, secondary Hypoparathyroidism, non-insulin-dependent diabetes mellitus (NIDDM), and hypogonadism were the commonest endocrine complications. Age of the patient and duration of disease were primary risk factors significantly affecting the prevalence of these complications. Highlights : High Prevalence of Endocrinopathies: 95.9% of Beta-thalassemia major patients had at least one form of endocrine disorder, indicating it as a major complication. Common Types Identified: Growth hormone deficiency, secondary hypoparathyroidism, non-insulin-dependent diabetes mellitus, and hypogonadism were the most frequent endocrinopathies. Risk Factors: Older age and longer disease duration were significantly associated with a higher prevalence of these endocrine complications. Keywords: Prevalence, Endocrinopathies, Beta Thalassemia Major